Estimation of symbiotically fixed nitrogen using extended N difference methods - Hauser, S. (1992)
There are limitation to all methods currently available for estimating symbiotically fixed nitrogen. This paper evaluates the I5N dilution and N difference methods, and reports on the results of field experiments conducted with faba beans (Viciafaha) and peas (Pisum sativum). The objectives of these experiments were to investigate whether the limitations of the N difference method, hitherto the least-used method, could be overcome, to study the effect of extending the simple N difference method, and to compare the preconditions of this extended method with those of the I5N dilution method. The extension of the N difference method from using only shoot nitrogen to include consideration of nitrogen in litter fall, roots and nodules increased the estimates of fixed nitrogen by 2 1 kg/ha (11%) for faba beans. Additional consideration of nitrate-N in the soil increased estimates of fixed nitrogen by 40 kg/ha (21%) for faba beans and by 33 kg/ha (18%) for peas. A comparison between the preconditions for the extended N difference method and the I5N dilution method showed them to be the same.